Martensitic transformation in free-standing Cu-Al-Ni thin films with micrometric grain size - Morán, Mauricio Javier (2019)
The martensitic transformation of polycrystalline thin films based on shape memory alloys is usually affected by the average grain size and by the thickness. We have carried out a study of the temperature driven martensitic transformation in micrometric grain size Cu-Al-Ni films with 18R structure. Thin films with a thickness of 6 μm were grown by sputtering on highly oriented pyrolytic graphite HOPG (0001) substrate at 873 K. After that, the samples were peeled-off from the substrate and annealed at 1123 K for 30 min. The observed microstructure shows an average grain size of 3.7 (± 0.2) μm. The martensitic start temperature (M s) for different films ranges from 170 K to 370 K due to small changes in the chemical concentration. The influence of surface oxides and changes in the atomic order produced by post-quench aging treatments is analyzed. The results show that while surface passivation has a weak influence, changes in the atomic order increase M s without impacting significantly on the hysteresis. Comparison with previous results of nanometric and micrometric grain size samples reveals that the barriers for the transformation are mainly given by plastic deformation at grain boundaries.